2009
DOI: 10.1007/s10801-009-0171-6
|View full text |Cite
|
Sign up to set email alerts
|

Regularity, depth and arithmetic rank of bipartite edge ideals

Abstract: We study minimal free resolutions of edge ideals of bipartite graphs. We associate a directed graph to a bipartite graph whose edge ideal is unmixed, and give expressions for the regularity and the depth of the edge ideal in terms of invariants of the directed graph. For some classes of unmixed edge ideals, we show that the arithmetic rank of the ideal equals projective dimension of its quotient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
79
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(81 citation statements)
references
References 13 publications
2
79
0
Order By: Relevance
“…(1) G is a sequentially Cohen-Macaulay bipartite graph (see [48]); (2) G is an unmixed bipartite graph (see [36]); (3) G is a very well-covered graph (see [38]); (4) G is a C 5 -free vertex decomposable graph (see [34], the case where G is also C 4 -free was proved in [5]). …”
Section: Small Regularity and Computing Regularitymentioning
confidence: 99%
“…(1) G is a sequentially Cohen-Macaulay bipartite graph (see [48]); (2) G is an unmixed bipartite graph (see [36]); (3) G is a very well-covered graph (see [38]); (4) G is a C 5 -free vertex decomposable graph (see [34], the case where G is also C 4 -free was proved in [5]). …”
Section: Small Regularity and Computing Regularitymentioning
confidence: 99%
“…Bounds on the regularity of edge ideals have been studied by a number of researchers (see [1], [2], [3], [4], [5], [6], [7], [8] [9], [11], [12], [13]). For example, Fröberg (see [3]) has shown that, when I(G) is the edge ideal of a graph whose complement does not have any induced cycle of size greater than or equal to four, then I(G) has linear minimal free resolution.…”
Section: Introductionmentioning
confidence: 99%
“…One goal of this research program is to relate algebraic properties and invariants of a squarefree monomial ideal to combinatorial properties and statistics of the corresponding simple hypergraph. In this note, we will examine the Castelnuovo-Mumford regularity of such ideals, which has been previously studied in work including [5,7,9,14,16,20,22].…”
Section: Introductionmentioning
confidence: 99%